The Impact of Covid -19 Pandemic in Development Banks’ Stock Performance Evidence from Nepal (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2024)
Propose: This study explores the relationship between COVID-19 and the stock market in Nepal from February 15th, 2020, to February 15th, 2023, with a focus on the impact on development banks. Adopting a descriptive research design, the study analyzes the risk and fluctuation in stock prices of development banks during the pandemic. The first half of 2020 witnessed a significant stock market crash due to the global spread of COVID-19 and subsequent economic disruptions caused by lockdowns.Methods: The study examines how different sectors within the stock market reacted to COVID-19, with sectors like natural gas and healthcare showing positive returns, while others like petroleum and entertainment experienced declines. It emphasizes the trade-off between risk and return in financial management, highlighting investors' demand for compensation for bearing risk.Findings: The findings suggest that development banks in Nepal faced increased risk and fluctuation in stock prices during the pandemic. However, the study also reveals opportunities for investors, as economic crises can create investment prospects. Contrary to some literature, the study indicates that the market index in Nepal showed positive correlations with the number of COVID-19 cases, deaths, recoveries, and active cases, suggesting no significant impact of COVID-19 on the stock market index.Values: This study contributes to understanding the dynamics of the stock market during crises like COVID-19 and provides insights for investors and financial analysts.DOI: https://doi.org/10.69476/sdpr.2024.v01i01.007